The RNA acetyltransferase driven by ATP hydrolysis synthesizes N(4)-acetylcytidine of tRNA anticodon - Ikeuchi, Yoshiho (Nature Publishing Group, 2008)
The wobble base of Escherichia coli elongator tRNA(Met) is modified to N(4)-acetylcytidine (ac(4)C), which is thought to ensure the precise recognition of the AUG codon by preventing misreading of near-cognate AUA codon. By employing genome-wide screen of uncharacterized genes in Escherichia coli (‘ribonucleome analysis'), we found the ypfI gene, which we named tmcA (tRNA(Met) cytidine acetyltransferase), to be responsible for ac(4)C formation. TmcA is an enzyme that contains a Walker-type ATPase domain in its N-terminal region and an N-acetyltransferase domain in its C-terminal region. Recombinant TmcA specifically acetylated the wobble base of E. coli elongator tRNA(Met) by utilizing acetyl-coenzyme A (CoA) and ATP (or GTP). ATP/GTP hydrolysis by TmcA is stimulated in the presence of acetyl-CoA and tRNA(Met). A mutation study revealed that E. coli TmcA strictly discriminates elongator tRNA(Met) from the structurally similar tRNA(Ile) by mainly recognizing the C27–G43 pair in the anticodon stem. Our findings reveal an elaborate mechanism embedded in tRNA(Met) and tRNA(Ile) for the accurate decoding of AUA/AUG codons on the basis of the recognition of wobble bases by the respective RNA-modifying enzymes.